Intelligent voice assistant as an example of inclusive design methodology implementation - A. A. Zakharov; I. G. Zakharova; A. M. Shabalin; Sh. I. Khanbekov; D. B. Dzhalilzoda (Russian State Vocational Pedagogical University, 2024)
Introduction. The development of artificial intelligence methods and technologies aimed at speech recognition contributes to the creation of specialised programmes - namely voice assistants - which are capable of conducting a dialogue in natural language. Such services are of particular relevance in inclusive education in order to support students with visual impairments. The research problem lies in the individualised support of students' independent work based on a voice assistant and is determined by the contradiction between the widespread use of various question-answer systems in business and everyday life (including those with a voice interface), on the one hand, and insufficient knowledge their didactic possibilities, on the other hand.Aim. The present research aims to investigate and practically implement the methodology of inclusive design of digital educational resources on the example of creating an intelligent voice assistant for students' independent work in the course "Computer Networks".Methodology and research methods. The current research is based on the methodology of inclusive design in combination with an ontological approach in relation to the creation of digital educational resources, speech recognition methods, methods for designing intelligent systems and knowledge bases, methods and technologies for designing and implementing automated learning systems with feedback. To recognise questions, search for answers, and support dialogues carried out by a voice assistant, the authors applied natural language text analysis methods and classification models created using machine learning methods.Results. The authors have developed and substantiated the requirements that a digital educational resource must meet in accordance with the principles of inclusive design, linking an ontological approach to content development, automatic individualised support for students, and monitoring the achievement of educational results. According to the formulated requirements, the authors have developed an interactive computer service - an intelligent voice assistant that provides support for students' independent work when performing practical tasks, using the "Computer Networks" course as an example. The service supports voice input and subsequent interpretation of questions, search for answers in the knowledge base with voice output of the result, and implements the execution of operations according to certain rules.Scientific novelty. The authors have clarified the content of the concept of "inclusive design" in the context of digital educational resources, when the key feature is the focus on continuous improvement of the didactic capabilities of a particular product. The authors have shown that this can be achieved through a conceptually based content structure and initially provided feedback. This approach has proven to be effective in designing an intelligent voice assistant to answer student questions and to automatically perform operations on a computer.Practical significance. The use of a voice assistant by students of the Institute of Mathematics and Computer Science of the University of Tyumen in the process of studying the course "Computer Networks" demonstrated the relevance of developing similar question-answering systems to accompany the independent work of students, including those with visual impairments in online and blended learning. The developed service is universal and can be used with any knowledge base that provides answers to students' questions.